Analysis and simulation of mathematical models for tumor therapy - Supadi, Subiyanto (Terengganu: Universiti Malaysia Terengganu, 2013)
There are many possible approaches to tumor treatment. The most common of tumor treatments today are immunotherapy, chemotherapy and biochemotherapy. The goal of these treatments does strengthen the body's own natural ability to combat cancer by enhancing the effectiveness of the immune system.